“May I Grab Your Attention?”: An Investigation Into Infants' Visual Preferences for Handled Objects Using Lookit as an Online Platform for Data Collection - Nelson, Christian M.; Oakes, Lisa M. (Frontiers in Psychology, 2021)
We examined the relation between 4- to 12-month-old infants’ (N = 107) motor development and visual preference for handled or non-handled objects, using Lookit (lookit.mit.edu) as an online tool for data collection. Infants viewed 8 pairs of objects, and their looking was recorded using their own webcam. Each pair contained one item with an easily graspable “handle-like” region and one without. Infants’ duration of looking at each item was coded from the recordings, allowing us to evaluate their preference for the handled item. In addition, parents reported on their infants’ motor behavior in the previous week. Overall, infants looked longer to handled items than non-handled items. Additionally, by examining the duration of infants’ individual looks, we show that differences in infants’ interest in the handled items varied both by infants’ motor level and across the course of the 8-s trials. These findings confirm infant visual preferences can be successfully measured using Lookit and that motor development is related to infants’ visual preferences for items with a graspable, handle-like region. The relative roles of age and motor development are discussed.